Effect of surface roughness of Chinese sub-bituminous coal on the kinetics of three-phase contact formation. (15th March 2018) - Wang, Shiwei; Guo, Jifeng; Tang, Longfei; He, Huan; Tao, Xiuxiang
Graphical abstract: Highlights: Low rank coal samples with hydrophilic and different rough surfaces were adopted. Three-phase contact lines on the low-rank coal rough surfaces were presented. Expansion velocity of three-phase contact decreased with surface roughness increase. Abstract: In this paper, terminal diameter and expansion velocity of the three-phase contact (TPC) line on the low-rank coal surfaces with different surface roughness were investigated. To eliminate the heterogeneity effect on the hydrophilic surfaces of low-rank coal particles, experimental samples with low ash content were adopted. Moreover, the analysis result of XPS indicated that there were few hydrophilic mineral particles on the low-rank coal surface. Furthermore, from the analyses of SEM and AFM measurements there are many crevices (pillars, protrusions) of different sizes (height and width) in different local areas of low-rank coal surfaces. Therefore, the three-phase contact lines on the low-rank coal surfaces presented different wetting behaviors. It demonstrated that the wetting film diameter became smaller and the expansion velocity of the three-phase contact line was faster while the surface roughness of low-rank coal samples increased.